Customer Advocacy: A Distinctive Form of Word of Mouth. (May 2020) - Sweeney, Jillian; Payne, Adrian; Frow, Pennie; Liu, Dan
Enthusiastic customer endorsements can significantly influence buying decisions and drive sales. In service contexts, advocates are especially important because the specific and complex characteristics of services make personal recommendations very effective. Customer advocacy communications differ from other positive word of mouth (PWOM), though literature on advocacy is surprisingly sparse and inconsistent. Notably, advocacy is strong, passionate, explicit, and ongoing, with an explicit goal of positively influencing others' views. As its central theoretical contributions, this article defines advocacy; identifies advocacy as a distinctive form of PWOM; conceptualizes advocacy according to a hierarchy of behaviors, which increase in intensity and effort; and develops a robust, reliable advocacy scale. By investigating positive behavioral outcomes of different levels of advocacy, this study also reveals the importance of identifying strong advocates, rather than just those who give PWOM, as well as salient drivers of advocacy. Accordingly, this article establishes a platform for further investigations of the importance of advocates, as well as recommendations to help managers identify these potentially valuable advocates.